Comparison of Social Phobia, Difficulty in Emotion Regulation, and Social Self-Efficacy in Individuals with Clinical Body Mass Index and Normal Weight - Golpour , Karim; Alizadeh , Somayeh; Alizadeh Darbandi, Hasan (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to determine the differences in social phobia, difficulty in emotion regulation, and social self-efficacy between individuals with clinical body mass index (BMI) and normal weight.Methods and Materials: A causal-comparative design was employed with two groups: 63 individuals with clinical BMI (recruited from nutrition counseling centers in Tehran’s District 3 during autumn/winter 2024–2025) and 64 normal-weight individuals. Validated instruments included the Social Phobia Inventory (SPIN; Connor et al., 2000), Difficulties in Emotion Regulation Scale (DERS; Gratz & Roemer, 2004), and Social Self-Efficacy Scale (SSES; Smith & Betz, 2000). Reliability coefficients (Cronbach’s α: 0.74–0.94) and validity were confirmed. Multivariate analysis of variance (MANOVA) in SPSS-26 tested group differences after verifying assumptions (Box’s test, Levene’s test).Findings: Significant differences emerged across all variables (*p* < .001). The clinical BMI group reported higher social phobia (M = 63.40 vs. 36.80; F(1,125) = 515.85, partial η² = 0.82) and emotion regulation difficulties (M = 69.10 vs. 41.69; F(1,125) = 847.58, partial η² = 0.88), and lower self-efficacy (M = 44.09 vs. 69.07; F(1,125) = 321.44, partial η² = 0.74) compared to the normal-weight group. Large effect sizes (η² = 0.74–0.88) underscored clinically meaningful disparities.Conclusion: These findings suggest that individuals with clinical BMI experience higher levels of social phobia and lower social self-efficacy compared to those with normal weight. Furthermore, they exhibit greater difficulties in emotion regulation.